Internal tide oceanic tomography - Zhongxiang Zhao (Geophysical Research Letters)
Abstract A concept of internal tide oceanic tomography (ITOT) is proposed to monitor ocean warming on a global scale. ITOT is similar to acoustic tomography, but that work waves are internal tides. ITOT detects ocean temperature changes by precisely measuring travel time changes of long‐range propagating internal tides. The underlying principle is that upper ocean warming strengthens ocean stratification and thus increases the propagation speed of internal tides. This concept is inspired by recent advances in observing internal tides by satellite altimetry. In particular, a plane wave fit method can separately resolve multiple internal tidal waves and thus accurately determines the phase of each wave. Two examples are presented to demonstrate the feasibility and usefulness of ITOT. In the eastern tropical Pacific, the yearly time series of travel time changes of the M2 internal tide is closely correlated with the El Niño–Southern Oscillation index. In the North Atlantic, significant interannual variations and bidecadal trends are observed and consistent with the changes in ocean heat content measured by Argo floats. ITOT offers a long‐term, cost‐effective, environmentally friendly technique for monitoring global ocean warming. Future work is needed to quantify the accuracy of this technique.